Handling of Connectivity Cases in Corruption Crimes in the Indonesian Army's Mandatory Housing Savings Program: Study of Verdict Number: 21-K/PMT-II/AD/II/2022 - Faisal, Adhiya; Bakhtiar, Handar Subhandi (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Criminal acts of corruption in the Indonesian Army's Mandatory Housing Savings Program (TWP TNI AD) are an example of a case involving both military and civilian legal subjects, triggering complex challenges in law enforcement in Indonesia. This study aims to examine the mechanisms for handling cases of connected criminal acts of corruption and the legal considerations in sentencing perpetrators based on the Jakarta High Military Court II Verdict Number 21-K/PMT-II/AD/II/2022. The research method employs a normative approach, analyzing relevant laws, legal doctrines, and jurisprudence. The results of the study show that cases are handled collaboratively between military and civilian institutions through the stages of investigation, inquiry, determination of the judicial forum, prosecution, and trial. The court's verdict confirmed that the defendants had been proven to have committed corruption together and continuously, resulting in state losses of Rp 127 billion, with sentences of imprisonment, fines, and restitution obligations. This study demonstrates the effectiveness of the connected justice system in ensuring justice and recovery of state losses, while also making an important contribution to the eradication of corruption in the military.